INFLUENCE OF REDUCTION IN HEAT OF ADSORPTION OF GAS ON NOISE IN GAS SENSORS - V. G. Paremuzyan; V. M. Aroutiounian
Recently we have published several papers where noise spectroscopy might be highly useful for improving gas sensors sensitivity and selectivity. In this paper, we continued the theoretical description of adsorption–desorption noise in gas sensors. Using the Langmuir's isotherm, we derived an expression for the adsorption–desorption noise in the case when the heat of the adsorption is reduced. We have analyzed dependence of the amplitude and cut-off frequency of the power density spectrum of the noise on parameters of sensor and gas. Application of the proposed model for simulating the oxygen chemisorptions-induced noise is very important because we have shown recently experimentally the possibility of fluctuation-enhanced gas sensitivity.
Keywords: Physics; Electronic structure and electrical properties of surfaces